DAMPAK GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA KANTOR TUKANG KIRIM CABANG SURABAYA - Anggita Putri Ananda; Etin Puspita Sari; Fianita Malati; Mochamad Fatchurrohman (Media Mahardhika, 2023)
Writing this article aims to find out the impact or leadership aty on the work of the Surabaya branch delivery workers,to achieve the employee performance goals expected by the company, a leader must be able to unite himself to subordinates or employees in order to create a good bomd beetwen leaders and subordinates. To achieve this goal, of course, it is not only to leader who carriesout the work bond, but the subordinates or employees must also support each other. Members are expected to manage good workers so that they can rely on them for the members’ goals, because managing bad workers is bad for the company and business achievements. In this study using qualitatif research with data collection techniques through field studies by means of interviews.